2002
DOI: 10.1046/j.1439-037x.2002.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of NaCl and Polyethylene Glycol on Germination, Emergence and Seedling Growth of Cowpea

Abstract: Seeds of Pacen˜o and Cuarenten˜o cultivars of cowpea (Vigna unguiculata L. Walp.) were tested for salt and drought tolerance at germination, seedling emergence and early seedling growth in NaCl and PEG-8000 solutions of different osmotic potentials (0, )0.2, )0.4, )0.6, and )0.8 MPa). Daily and final germination and emergence percentage, as well as germination and seedling emergence rate, and seedling growth were recorded under controlled conditions. Results showed that germination and emergence rate were dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
102
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 44 publications
26
102
0
5
Order By: Relevance
“…The results obtained in this study revealed that dry weights were less affected than fresh weights and are in agreement with the results obtained by Murillo-Amador (2002) in cowpea. The effect of PEG on the leaf area of 10-days-old plants was greater than that on fresh and dry weights and plant height (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in this study revealed that dry weights were less affected than fresh weights and are in agreement with the results obtained by Murillo-Amador (2002) in cowpea. The effect of PEG on the leaf area of 10-days-old plants was greater than that on fresh and dry weights and plant height (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, salt and water stresses are responsible for either inhibition or delayed seed germination and seedling establishment (Bewley & Black 1994). Under stress conditions, the germination of seeds is affected by creating an external osmotic potential that prevents water uptake or due to the toxic effects of Na + and Cl -ions both during imbibition and seedling establishment (Murillo-Amador 2002).…”
mentioning
confidence: 99%
“…como o Na + e o Cl - (Murillo-Amador et al 2002, Khajeh-Hosseini et al 2003. Os íons e o estresse osmótico são responsáveis tanto pela inibição quanto pela demora na germinação e estabelecimento das plântulas (Almansouri et al 2001).…”
Section: Abstract Resumounclassified
“…
INTRODUÇÃOO avanço da área de cultivo de soja vem ocorrendo em todas as regiões do País (Conab 2014), especialmente no Nordeste, que possui a maior concentração de solos salinos e baixos índices pluviométricos (Cirilo et al 2010).Os solos salinizados ocorrem em condições topográficas que não favorecem uma drenagem eficiente, principalmente onde o manejo da irrigação é inadequado ou a água utilizada apresenta problemas de qualidade (Oliveira 1997).A salinidade do solo pode comprometer a germinação das sementes pela diminuição do potencial osmótico externo, impedindo a absorção de água, ou por meio dos efeitos tóxicos da absorção de íons
ABSTRACT RESUMOcomo o Na + e o Cl - (Murillo-Amador et al 2002, Khajeh-Hosseini et al 2003. Os íons e o estresse osmótico são responsáveis tanto pela inibição quanto pela demora na germinação e estabelecimento das plântulas (Almansouri et al 2001).
…”
unclassified
“…This may be due to the reduction in water absorption during the imbibition phase or the excessive absorption of toxic ions, especially Na + and Cl - (Prisco and O'Leary, 1970), which alter metabolism by inhibiting or delaying mobilization of storage reserves and damaging the membrane system of the embryonic axis (Prisco et al, 1981;Gomes-Filho and Prisco, 1983;Chartzoulakis and Klapaki, 2000;Murillo-Amador et al, 2002).…”
Section: Cashew Seed Germination and Seedling Establishmentmentioning
confidence: 99%